The Incidence Rate of Nervous System Disorders in Patients Above the Age of 65 - Monika Biercewicz; Kornelia Kędziora-Kornatowska (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. The most frequent diseases of people aged 60 or over are the diseases of cardiovascular system, musculoskeletal disorders and metabolic diseases. In the case of long-lived people the biggest risk is posed by acute inflammation and infections (e.g. pneumonia, flu) as well as the consequences of falls and broken bones. Among many factors, that significantly affect psychophysical capacity of these people, there should be mentioned health factors (e.g. diseases, some systems and organ disorders). This group also comprises nervous system disorders such as: vascular diseases, dementia and extrapyramidal disorders. Aim. The aim of this work was to assess the incidence rate of the nervous system disorders and their influence on the psychophysical condition of people aged 65 or over. Material and Methods. We conducted the study in the Clinic of Geriatrics Bydgoszcz, Poland. Participants included 127 patients hospitalized due to disease process. The criterion used for the selection of research participants was their age. They were divided into three subgroups in accordance with the subperiods distinguished by UNO (United Nations Organization): 65-74 (early old age), 75-89 (advanced old age), 90 and more (longevity). The scale used in the research is the standard scale that is most frequently used in nursing and clinic practice both in Poland and worldwide. We used the Activities of Daily Living (ADL) scale to assess everyday activities, Timed Up&Go Test (Up&Go) was used to assess the risk of falls, Geriatric Depression Scale (GDS) was used to point the risk of worsening of depression symptoms and Mini Nutritional Assessment (MNA) to assess the nutritional condition of the participants. The data that refers to sociodemographic and clinic variables was collected with the use of structured form used for data collection. Results. The statistical analysis of the influence of the clinical diagnosis on psychophysical assessment of people aged over 65 showed that this factor is statistically significant (p=0.031) only with reference to functional condition assessed with the use of ADL scale. The results of the Up&Go scale (p=0.214), MNA (p=0.324) and GDS (p=0.071) were not statistically significant. Conclusions. The nervous system disorders were classified for the second place in the context of polipathology which is characteristic for elderly people. In the research group the main disease, due to which the patient is hospitalized, did not significantly influence the psychophysical condition of people over the age of 65. (JNNN 2015;4(3):96–101)